Rational Illiquidity and Consumption: Theory and Evidence from Income Tax Withholding and Refunds - Gelman, Michael; Kariv, Shachar; Shapiro, Matthew D.; Silverman, Dan (American Economic Review, 2022)
Low liquidity and a high marginal propensity to consume are tightly linked. This paper analyzes this link in the context of income tax withholding and refunds. A theory of rational cash management with income uncertainty endogenizes the relationship between illiquidity and the marginal propensity to consume, and can explain the finding that households tend to spend tax refunds as if they valued liquidity, yet do not act to increase liquidity by reducing their withholding. The theory is supported by individual-level evidence based on financial account records, including a positive correlation between the size of tax refunds and the marginal propensity to consume out of those refunds. (JEL E21, G51, H24, H31)